2007
DOI: 10.1007/s00210-007-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Indirect role of α2-adrenoreceptors in anti-ulcer effect mechanism of nimesulide in rats

Abstract: Nimesulide, a non-steroidal, anti-inflammatory drug, produces ulcerogenic effects in adrenalectomized rats but is gastro-protective in intact rats. The objective of this study was to determine whether adrenal gland hormones are involved in the anti-ulcer effects of nimesulide. The results revealed that 100 mg/kg nimesulide produces gastric ulceration in adrenalectomized rats, which is prevented by prednisolone and adrenaline. The anti-ulcer effects of adrenaline and prednisolone in adrenalectomized rats were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 24 publications
0
49
0
Order By: Relevance
“…These findings indicate that the level of adrenalin must be low for an antiinflammatory effect to be observed. Furthermore, in our previous study nimesulide demonstrated antiinflammatory and anti-ulcerative activities resulting from decreased adrenalin levels [31]. In light of these observations we suggest that drugs that decrease adrenalin levels may also have anti-inflammatory and anti-ulcerative effects.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…These findings indicate that the level of adrenalin must be low for an antiinflammatory effect to be observed. Furthermore, in our previous study nimesulide demonstrated antiinflammatory and anti-ulcerative activities resulting from decreased adrenalin levels [31]. In light of these observations we suggest that drugs that decrease adrenalin levels may also have anti-inflammatory and anti-ulcerative effects.…”
Section: Introductionmentioning
confidence: 61%
“…In previous studies metyrosine was shown to reduce circulating adrenalin levels significantly [22,31]. As mentioned previously, NSAIDs create an anti-inflammatory effect by reducing adrenalin levels [27].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…25 Prednisolone, a glucocorticoid, produces ulcers in healthy intact rats and prevents ulcer formation in both adrenalectomized (endogenous adrenaline has been eliminated) rats and in intact rats that have received metyrosine (with reduced endogenous adrenaline). 26 Black (1988), Wallace (1987) and Weusten et al, 1993, demonstrated in their studies that glucocorticoids increase ulcer incidence in both human and animal subjects. [27][28][29] In our above-mentioned study, we showed that prednisolone produced antiulcer effects via the a2-adrenoreceptors in the absence of adrenaline in adrenalectomized rats, and in the presence of reduced adrenaline concentrations in rats given metyrosine.…”
mentioning
confidence: 98%